Campus solidarity campaign: respect and support for students with mental illness. Issue 4 (9th November 2015) - Kosyluk, Kristin; Schmidt, Annie; Abelson, Sara; Malmon, Alison; Corrigan, Patrick
Abstract : Purpose: – The purpose of this paper is to describe the evaluation of a set of potential logos for a campaign aimed at promoting an environment of solidarity and support on college campuses for students with mental illness. Design/methodology/approach: – Participants completed an online survey responding to statements about college students and mental illness by selecting the logo they thought best represented each statement. Findings: – One-sample χ 2 tests were conducted to assess difference in frequency of brand endorsement by statement. Research limitations/implications: – Through use of the scientific method to evaluate three potential logos designed to represent this campaign, it is more likely that the campaign will have its intended impact, and avoid potential deleterious effects. Limitations of the study include the representativeness of the sample, and the fact that endorsement of statements may not translate to behavior, the ultimate outcome of interest. Future studies should include population research strategies. Practical implications: – A campaign such as the one described here, with a scientifically selected brand, may have a greater effect on stigma surrounding mental illness, a significant public health concern. Originality/value: – This is the first study of its kind to scientifically evaluate the brand for an anti-stigma program. The findings of this study would be of value to advocates, college and university administrators, staff, and educators, and college student with mental illness seeking to promote supportive environments on college and university campuses for students with mental illness.